Proceedings of the 1992 ACM Conference on Computer-Supported Cooperative Work - CSCW '92 1992
DOI: 10.1145/143457.143476
|View full text |Cite
|
Sign up to set email alerts
|

A collaborative medium for the support of conversational props

Abstract: Our work focuses on providing computational support for informal communication among people who are geographically separated. To better understand the use of artifacts in communication, we looked at the contents of office whiteboards after they had been used in conversations. Our analysis revealed that whiteboards are used to present and discuss various classes of objects with specific semantic properties. We call these objects "conversational props," and we have come to think of a whiteboard as a conversation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…Shared drawing systems such as Tivoli (Pedersen, McCall, Moran, & Halasz, 1993), Conversation Board (Brinck & Gomez, 1992), and DOLPHIN (Streitz, Geissler, Haake, & Hol, 1994) allow participants to use styli to mark on the shared drawing. Although many drawing tools were designed primarily to support the creation of shared images (e.g., architectural diagrams or design sketches), studies of their use have observed the importance of the tools for gestural communication.…”
Section: Implementing Gesture In Video Systems For Remote Collaborationmentioning
confidence: 99%
“…Shared drawing systems such as Tivoli (Pedersen, McCall, Moran, & Halasz, 1993), Conversation Board (Brinck & Gomez, 1992), and DOLPHIN (Streitz, Geissler, Haake, & Hol, 1994) allow participants to use styli to mark on the shared drawing. Although many drawing tools were designed primarily to support the creation of shared images (e.g., architectural diagrams or design sketches), studies of their use have observed the importance of the tools for gestural communication.…”
Section: Implementing Gesture In Video Systems For Remote Collaborationmentioning
confidence: 99%
“…They share information placed on this surface, use objects on the table as conversational props, or develop ideas and work products (Tang 1991;Brinck and Gomez, 1992). In contrast, desktop computers may inhibit the group interaction, even though they potentially allow access to information and productivity tools pertinent to the task at hand.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve an awareness of the workspace, team members use a combination of verbal and visual communication as their primary source of information (Brinck & Gomez, 1992;Gutwin & Greenberg, 2002b). Verbal communication can include either explicitly talking about one's work activity and the position held or by overhearing others' conversation.…”
Section: Workpace Awareness and Couplingmentioning
confidence: 99%